Differences in motor recovery between upper and lower limbs: does stroke subtype make the difference?. Issue 2 (June 2016) - Paci, Matteo; Nannetti, Luca; Casavola, Davide; Lombardi, Bruna
Abstract : Previous studies comparing the patterns of recovery for upper (UL) and lower limbs (LL) reported similar patterns of motor recovery of extremities. However, the influence of clinical stroke subtypes on the difference between recovery of extremities has never been investigated. The aim of this study is to compare the time course of the UL and LL in a sample of patients who have had distinct subtypes of ischemic stroke. A total of 443 consecutive patients following ischemic stroke were assessed at admission, discharge, and 1 month after discharge with the arm and leg motor parts of the Fugl-Meyer scale. Separate analyses were carried out for the entire sample and for samples of each stroke subtype classified according to the Oxfordshire Community Stroke Project. All groups showed significant improvements in motor function ( P <0.001). Within the group of patients with total anterior circulation infarcts, the LL showed greater improved motor recovery than the UL ( P <0.001). No significant difference was found between the time course of UL and LL motor recovery in the entire sample and in the other groups. This study confirms similar motor recovery of limbs in the entire sample, but also shows that the LL has greater recovery than the UL in patients with total anterior circulation infarcts. Functional prognosis should take into account the distinct stroke subtypes.